Microespaço: comunicação e produção de conhecimento no ciberespaço - Silva, Caio Roberto Balieiro e (2011)
Social net phenomenon is not new. Since the beginning of BBS (Bulletin Board System), around 1978, people connects to internet to communicate, talk about curiosities and fait divers, create, are listened and feel part of a community, in a democratic platform. This study aims at analyzing the communicational nature of Twitter, approaching the relationships that can be found in messages exchanges between its members. This study is organized in three parts. The first one beggins with the definition of microspace, recovering primitive ways of communication, limited by the environment, evoluting to the first mass communication invention, the telegraph. Then, this study introduces the definition of microspace related to cyberspace s concepts proposed by Lévy and approaches the individual interest on herding, as Maffesoli said. The second part is about the poetics of cyberspace, redeeming the definition of microspace, now in other media, such as the haikais (Campos). The study sails in the cyberspace, through media culture (Santaella), net s labyrinth (Leão), translations (Plaza) and it docks in social nets (Rheingold), focusing on Twitter. Throughout the collection of material, this study exposes the communication s nature and objective found in microspace. At last, the third part presents the characteristics of net communication (Flusser and Shannon), the process of knowledge and learning generated by this kind of communication (Piaget e Freire) and it proposes a discussion on broad and restrict knowledge (Morin). The conclusions of this study may contribute to the identification of the critical thought spread through the net, exposing how this thought sails in the cyberspace and is translated in new ideas and senses